Ultralow Threshold Lasing from Carbon Dot–Ormosil Gel Hybrid-Based Planar Microcavity - Ni, Yiqun (Nanomaterials (Basel), 2021)
The absence of an ideal solid matrix with resistance to harsh conditions for carbon dots (CDs) and high transmittance in the visible/near infrared region is the bottleneck in CD applications. In this study, we show that a stable rigid structure can be formed between CDs and organically modified silicates (ormosil) gel when CDs are incorporated into ormosil gel hybrids as a solid matrix. A high photoluminescence quantum yield (PLQY) of 63% is achieved at a 583 nm emission. Peak optical gain of the hybrids was found to be 67 cm(−1) at peak wavelength. Ultralow threshold (~70 W/cm(2)) lasing can also be demonstrated from a planar microcavity by using CD–ormosil gel hybrids as a gain medium.